Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1088/1757-899x/202/1/012097
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Chip Formation Feedrates of Various Steels in Low-Speed Milling Process

Abstract: Abstract.Milling is a process of metal removal by feeding the workpiece a rotating multitoothed cutter. The objective of the study was to investigate the chip characteristics (chip length, width, and thickness) during the milling process by varying the feedrates and the types of materials used based on an experimental approach. The chosen materials were AISI 1020, AISI 1045, AISI 1090, AISI D2, and AISI 4340 with a high-speed steel (HSS) as a cutter. In this work, the feedrates were varied of 5, 10, and 15 mm/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…The chip characteristics during the milling process by varying the feed rates and the types of materials used were investigated by Prasetyo [24].…”
Section: State Of the Artmentioning
confidence: 99%
See 1 more Smart Citation
“…The chip characteristics during the milling process by varying the feed rates and the types of materials used were investigated by Prasetyo [24].…”
Section: State Of the Artmentioning
confidence: 99%
“…The coefficients of regression functions have been calculated using the software MATLAB and their significance was tested according to the Student's criterion. The regression functions (23) and (24) have been built. According to the Fisher-Snedecor-tested criterion, they describe the experiment adequately, while the reliability of the relations is R 2 = 0.91 and 0.94, respectively: a) For orthogonal cutting:…”
Section: Temperature Measuringmentioning
confidence: 99%
“…Along with an evolution of new materials that should be machined and continual cutting tools improvements, the topic of chip formation and its morphology is still relevant, so many researchers are presently addressing this issue. Prasetyo and Tauviqirrahman [28] developed more comprehensive models by using a power-law flow stress equation, whose coefficients are dependent on strain rate and temperature. These effects were combined using the concept of velocity-modified temperature, and it was suggested that the flow stress for a particular material at a given strain can be assumed to be a unique function of this parameter.…”
Section: State Of the Artmentioning
confidence: 99%
“…Planing is a cutting process in which the formed chip is visible to the eye, whereas in broaching, the chip generation process is hidden and invisible to the naked eye. Therefore, it is possible to monitor the development of the temperature field in the area of chip generation during planing with a temperature measuring device by laser aiming and thus providing an approximate idea of the temperature generated not only during cutting but also during broaching [1,2].…”
Section: Introductionmentioning
confidence: 99%